Percepções de professores universitários sobre seu papel na adaptação de alunos ao ensino superior - Basso, Fabiola de Cássia Reghelin (2018)
This Master’s Dissertation aimed at investigation how Brazilian higher education professors perceive students’ university adaptation. Two studies were conducted. In the absence of studies published on university adaptation from the professors' standpoint, we carried out a literature review on university adaptation in general. An integrative review on journal articles published in Portuguese was carried out about the process of university adaptation, adjustment, and integration. Seventeen studies were part of the final sample for further analysis, published between 2006 and 2016, selected from databases ScIELO, PePSIC and LILACS. The selection criteria demanded the paper to be a scientific article, written in Portuguese, and published in a peer-reviewed journal. The analyses showed university professors exert important influences on students’ academic adjustment, more specifically as to theoretical knowledge and educational, motivational, and interpersonal skills. Openness to dialogue and dedication to students’ academic adaptation and professional education are fundamental dispositions for professors to help students in their academic adaptation. The second study investigated how university professors perceive students’ academic adaptation to higher education. We interviewed 16 professors, men and women, aged between 34 and 69 years old, from different knowledge areas. Teaching experience ranged from two and a half to 39 years. The qualitative analysis conducted on data was by descriptive coding and categorization in groups of codes similar in meaning. Two sets of results yielded from the analysis: professors’ perceptions of students’ academic adaptation, and professors’ suggestions on how they may help students succeed in academic adaptation. The most significant contents derived from the analyses on the teachers' perceptions of what influence students' academic adaptation were: students' interpersonal relationships; teachers' behavior towards students' adaptation; and students' behavior towards their academic adaptation. One of the main roads to take for the future is to prepare students for the transition from high school to university and prepare professors to deal with students' academic adaptation challenges.